Mens en Omgeving (3) : Beelden en tekens. - De Beyerd, Breda (Breda : De Beyerd, 1982)
Boezem, Marinus ; Abel, L. ; Engels, Pieter ; Hubert, Pierre ; Lixenberg, Cyril ; van Munster, Jan ; Navez, Jean-Marc ; Noorbergen, Jo ; Peeter, Zoltin ; Van Rafelghem, Paul ; Van Snick, Philippe ; Struik, Mieke ; Verbist, Luc ; Buisman, Sjoerd
Mens en Omgeving (3) : Beelden en tekens, De Beyerd, Breda, 10 juli tot en met 3 oktober 1982
boek